The Needs of Continuous Professional Development Perceived by Novice and Experienced Teachers - Andista A.F. Anggraeni; Sri Rachmajanti (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study was intended to investigate the current needs of continuous professional development viewed from the eyes of novice and experienced teachers in Malang senior high schools. The study was conducted through a descriptive survey study. The results identified some similarities and differences of needs between the novice and experienced teachers. Based on the order of importance, novice teachers agree that they need professional development in (1) knowledge and understanding of learner's characteristics and (2) pedagogical competencies in teaching the subject field, (3) knowledge about curriculum or syllabus, (4) teacher's communication skill in the classroom, and (5) teaching and learning approaches. Meanwhile, the experienced teachers need CPD about (1) knowledge and understanding of learner's characteristics, (2) pedagogical competencies in the subject, (3) Information and Communication Technology, (4) students' evaluation and assessment, and (5) teaching and learning approaches. Knowing the findings above, policy makers are suggested to arrange CPD programs based on the teachers' needs and learning styles. The suitability and effectiveness of the program must be put into consideration. Abstrak: Penelitian ini mengungkap kebutuhan Pengembangan Keprofesian Berkelanjutan guru dilihat dari sudut pandang guru pemula dan berpengalaman di sekolah menengah atas di wilayah Malang. Penelitian menggunakan metode survei deskriptif. dan hasilnya menemukan bahwa terdapat persamaan dan perbedaan kebutuhan diantara guru pemula dan berpengalaman. Berdasarkan tingkat prioritas, PKB yang diperlukan guru pemula saat ini (1) pengetahuan tentang karakter peserta didik, (2) kompetensi pedagogik dalam mengajar, (3) pengetahuan tentang kurikulum atau silabus, (4) keterampilan berkomunikasi di kelas, (5) pendekatan belajar pembelajaran. Di lain pihak, guru berpengalaman memerlukan PKB tentang (1) pengetahuan tentang karakter peserta didik, (2) kompetensi pedagogik dalam mengajar, (3) penggunaan TI di dalam pengajaran, (4) penilaian peserta didik, (5) pendekatan belajar pembelajaran. Dengan mengetahui hal-hal diatas hendaknya pembuat kebijakan merancang program PKB berdasarkan kebutuhan dan gaya belajar masing-masing guru. Aspek kecocokan dan keefektivitasan program Pengembangan Keprofesian Berkelanjutan perlu diperhatikan.